Current Prophylaxis and Treatment Approaches for Acute Graft-Versus-Host Disease in Haematopoietic Stem Cell Transplantation for Children With Acute Lymphoblastic Leukaemia - Wölfl, Matthias; Qayed, Muna; Benitez Carabante, Maria Isabel; Sykora, Tomas; Bonig, Halvard; Lawitschka, Anita; Diaz-de-Heredia, Cristina (Frontiers in Pediatrics, 2022)
Acute graft-versus-host disease (aGvHD) continues to be a leading cause of morbidity and mortality following allogeneic haematopoietic stem cell transplantation (HSCT). However, higher event-free survival (EFS) was observed in patients with acute lymphoblastic leukaemia (ALL) and grade II aGvHD vs. patients with no or grade I GvHD in the randomised, controlled, open-label, international, multicentre Phase III For Omitting Radiation Under Majority age (FORUM) trial. This finding suggests that moderate-severity aGvHD is associated with a graft-versus-leukaemia effect which protects against leukaemia recurrence. In order to optimise the benefits of HSCT for leukaemia patients, reduction of non-relapse mortality—which is predominantly caused by severe GvHD—is of utmost importance. Herein, we review contemporary prophylaxis and treatment options for aGvHD in children with ALL and the key challenges of aGvHD management, focusing on maintaining the graft-versus-leukaemia effect without increasing the severity of GvHD.